2018
DOI: 10.1088/1757-899x/308/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Effective height of chimney for biomass cook stove simulated by computational fluid dynamics

Abstract: Abstract. This paper presents the results of numerical modelling of temperature distribution and flow pattern in a biomass cooking stove using CFD simulation. The biomass stove has been designed to suite the household cooking process. The stove consists of two pots. The first is the main pot located on the top of the combustion chamber where the heat from the combustion process is directly received. The second pot absorbs the heat from the exhaust gas.A chimney installed at the end of the stove releases the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Faisal et al present numerical modeling of temperature distribution and flow pattern in a biomass cooking stove using CFD simulation. Results showed that the chimney height at the highest temperatures is 1.65 m, which was validated by developing a model for computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Faisal et al present numerical modeling of temperature distribution and flow pattern in a biomass cooking stove using CFD simulation. Results showed that the chimney height at the highest temperatures is 1.65 m, which was validated by developing a model for computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%